Epidermoid Tumor of the Cerebellopontine Angle Presenting with Selective Sudden Hearing Loss. Intraoperative Evidence of a Pearl Tumor Infiltrating and Compressing the Cochlear Nerve - Alfieri, A.; Simmermacher, S.; Prell, J.; Strauss, C.; Scheller, C. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2012)
Epidermoid tumors of the cerebellopontine angle are associated with a variety of symptoms, usually attributed to compression and displacement of involved cranial nerves. The authors present a case of a large epidermoid tumor in the left cerebellopontine angle with sudden hearing loss and tinnitus. The intraoperative finding of migration of two tumor pearls into the cochlear nerve was the origin of the clinical sign. The patient improved remarkably after removal of the tumor. This case demonstrates the mechanism for selective hearing loss associated with the large cerebellopontine angle.
Keywords: epidermoid tumors; hearing loss; cerebellopontine angle